Complete filaggrin deficiency in ichthyosis vulgaris is associated with only moderate changes in epidermal permeability barrier function profile - Perusquía Ortiz, Ana María; Oji, V.; Sauerland, M.c.; Tarinski, T.; Zaraeva, I.; Seller, N.; Metze, D.; Aufenvenne, K.; Haußer-Siller, Ingrid; Traupe, H. (Journal of the European Academy of Dermatology and Venereology, 2013)
Background: Ichthyosis vulgaris (IV) is caused by loss-of-function mutations in the profilaggrin (FLG) gene. Filaggrin drives complex interrelated functions, with strategic roles in establishing structural and chemical barrier function, hydration of the skin and maintaining epidermal homeostasis. Data on the effect of FLG mutations on epidermal barrier function in IV are very scarce. Objectives: A primary aim of this study was to determine in vivo characteristics of epidermal permeability barrier function such as transepidermal water loss (TEWL), skin hydration and skin surface pH in homozygous or compound heterozygous (FLG−/−) and heterozygous (FLG+/−) subjects with IV. Methods: We evaluated a cohort of 15 patients with IV, analysed epidermal ultrastructure and investigated epidermal barrier function by measurement of TEWL, skin surface pH and skin hydration. Mutations were screened by restriction enzyme analysis and/or complete sequencing. Ten patients were homozygous or compound heterozygous (FLG−/−), while five patients were heterozygous (FLG+/−). Twenty healthy individuals served as controls. Results: In FLG−/− subjects, a moderate increase of TEWL from 5.41 ± 0.32-7.54 ± 0.90 g/m2h (P < 0.03) and a moderate decrease of skin hydration from 29.20 ± 1.96 to 20.17 ± 3.60 (P < 0.05) in comparison with the control group were observed. Changes in skin surface pH were not significant. FLG+/− subjects did not suffer from significant changes in all variables. Conclusions: A complete, but not a partial deficiency is associated with moderate changes in TEWL and skin hydration, revealing surprisingly only a mild disturbance of the epidermal permeability barrier function.
Gesehen am 10.01.2022